2017
DOI: 10.1016/j.biocon.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of oil palm expansion on avian biodiversity in a Neotropical natural savanna

Abstract: The consequences of converting tropical rainforest to oil palm are well-documented, but the impacts of oil palm conversion on natural savanna landscapes remain little-known. Natural savannas in South America have been identified as fertile grounds for future oil palm expansion, partly due to perceived low biodiversity impacts relative to forest systems. We quantify the impacts of oil palm conversion for bird communities inhabiting natural savannas in the Colombian Llanos. Bird species richness and abundance we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 88 publications
4
11
0
1
Order By: Relevance
“…We hypothesize then, that oil palm can promote the presence of potential prey, such as lizards, frogs, small rodents, snakes, birds, and arthropods, which has been reported in oil palm ecosystems (e.g. [ 83 ][ 84 ][ 96 ][ 97 ][ 98 ]). In this way, these mesopredators could be acting as biological control agents for potential pest species [ 82 ] and thus potentially assisting plantation management.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize then, that oil palm can promote the presence of potential prey, such as lizards, frogs, small rodents, snakes, birds, and arthropods, which has been reported in oil palm ecosystems (e.g. [ 83 ][ 84 ][ 96 ][ 97 ][ 98 ]). In this way, these mesopredators could be acting as biological control agents for potential pest species [ 82 ] and thus potentially assisting plantation management.…”
Section: Discussionmentioning
confidence: 99%
“…This general pattern is consistent with comparable results on the local avifauna surveyed within the same forest landscape, which showed that oil palm plantations were more impoverished in species composition than cattle pastures, secondary forests and primary forests within the same region[ 23 ]. In another study in natural savannas of the Colombian Llanos, species richness and abundance were severely reduced in areas converted into oil palm, and there were marked difference in species composition between habitats[ 24 ]. In contrast, a study in the Colombian Amazon showed that ants, dung beetles, and birds were more diverse in oil palm plantations than in pasture areas, and that oil palm could support a wide range of forest species[ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Faunal diversity responses to these structural changes depending on both the landscape context of plantations and species ecological plasticity in terms of tolerance to a severely modified habitat[ 19 ][ 20 ][ 21 ]. Ecological studies addressing multiple taxa, including birds[ 20 ][ 21 ][ 22 ][ 23 ][ 24 ], reptiles[ 20 ], non-flying small mammals[ 25 ], bats, primates[ 26 ], butterflies[ 27 ], ants[ 28 ] and aquatic invertebrates[ 29 ], have all shown that oil palm plantations are significantly more depauperate than adjacent primary forests, even if these had been selectively-logged[ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…3033 ). Although, investigations into the potential impacts of oil palm production on Colombian fauna have recently increased 32,3437 , there is still a paucity of information evaluating mammal species responses to oil palm plantations. This information is important, since the capacity of protected areas to function as a mechanism for biodiversity conservation in the long-term is limited, given the increasing rate of degradation occurring in these areas 38,39 , and the surrounding landscapes 40,41 .…”
Section: Introductionmentioning
confidence: 99%